2014
DOI: 10.4314/bajopas.v6i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and antibacterial properties of garlic extracts

Abstract: The antibacterial potency of aqueous and methanol extracts of garlic was determined invitro against three bacterial isolates (Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa) by agar well diffusion method. Preliminary phytochemical screening revealed the presence of tannin, flavonoid, carbohydrate, protein, saponin, alkaloid and glycoside in the plants while anthraquinone was absent. Both the aqueous and methanol extract of garlic were observed to be more potent against E. coli with maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 11 publications
2
10
1
4
Order By: Relevance
“…MBC values of garlic extracts when compared to that of ginger extracts are considerably low suggesting that garlic had higher activity in vitro against the test organisms as reported by Aliyu et al (2017). The n-hexane extracts were found to be more potent than the methanolic extracts which is in contrast to findings by Garba et al (2013). This accounts for the effect of the solvent system, which greatly affects the antibacterial activity of the crude extracts.…”
Section: Discussioncontrasting
confidence: 59%
“…MBC values of garlic extracts when compared to that of ginger extracts are considerably low suggesting that garlic had higher activity in vitro against the test organisms as reported by Aliyu et al (2017). The n-hexane extracts were found to be more potent than the methanolic extracts which is in contrast to findings by Garba et al (2013). This accounts for the effect of the solvent system, which greatly affects the antibacterial activity of the crude extracts.…”
Section: Discussioncontrasting
confidence: 59%
“…) and MIC value of the methanolic extract of garlic root (commonly used as spice and to treat many diseases) against S. aureus was 100 mg/mL (Garba et al . ). Overall, our findings confirmed that the methanolic extract of Apple kul has the potential to be used against P. aeruginosa and S. aureus infections.…”
Section: Resultsmentioning
confidence: 97%
“…These MIC values were similar with many other medicinal plants, e.g., MIC value of essential oil extracted from leaves of Hyptis pectinata (used as a traditional medicine and commonly distributed throughout America, West Africa and Western India) against P. aeruginosa was 200 mg/mL (Santos et al 2008). Zehneria scabra (traditionally used as medicinal plant) leaf extract MIC value against E. coli was 250 mg/mL (Abew et al 2014) and MIC value of the methanolic extract of garlic root (commonly used as spice and to treat many diseases) against S. aureus was 100 mg/mL (Garba et al 2014). Overall, our findings confirmed that the methanolic extract of Apple kul has the potential to be used against P. aeruginosa and S. aureus infections.…”
Section: Micmentioning
confidence: 99%
“…Garlic extract; Antimicrobial effect; Antioxidant Effect; feed additive reported to be effective against gram-positive, gram-negative, and 5]. Garba et al [7] reported that the minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) of water extracts of garlic for Escherichia coli were 100 and 200 mg/mL, respectively. Saha et al [8] reported that the MIC of garlic water extract (produced by extracting garlic with ATCC 52922 was 700 μg/mL.…”
Section: -331mentioning
confidence: 99%
“…Among these plants, garlic has been reported to exhibit various pharmacological effects: improvement of arteriosclerosis cancer, antiviral, and antioxidant activities; enhancing immunity and blood coagulation; lic has been reported to be effective against gram acid bacteria [3][4][5]. Garba et al [7] reported that the minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) of water extracts of garlic for were 100 and 200 mg/mL, respectively. Saha et al [8] reported that the MIC of garlic water extract (produced by extracting garlic with water)for E. coli ATCC 52922 was 700 compared the antimicrobial activities of garlic ethanol extr concentrations of 6.25, 12.5, 25, 50, and 100%.…”
Section: Introductionmentioning
confidence: 99%